Food in the lunchboxes of infant students of four public schools of Lima - Mamani-Urrutia, Víctor A. (2018)
Mr. Editor, Recently, the Manual of Advertising Warnings (MAP) was approved, putting an end to a long road of comings and goings for the implementation of Law N ° 30021, Law of Promotion of Healthy Eating for Children, Girls and Adolescents, although it is established that after 12 months of approval of the MAP, it will come into force; that is, in June 20191. This leaves a short time for the institutions that regulate and implement health policies in our country to prepare for the effects of the implementation of the aforementioned law. We believe that the debate with the population on other aspects of the law that are very important has not been deepened; thus, it is necessary to address the promotion of healthy eating and nutritional education in educational institutions jointly between the Ministry of Health and the Ministry of Education2. Nutrition education in preschool and school is essential to prevent the increase in overweight and obesity in children, since in 2014 the prevalence of obesity in children under 5 years was 9.3% and schoolchildren it reached 14.8%.